Clinical profile and the outcome of corrosive injury of GI tract - Velayudham, Rajendran; S., Senthilkumar; Karthikeyan, R. K. (International Journal of Research in Medical Sciences, 2017)
Background: Corrosive substances are common household substances that can be ingested either accidentally or intentionally with suicidal intent. The present study was conducted to analyse the clinical profile of 50 cases of corrosive injury of GI tract and to analyse the outcome of 50 cases of corrosive injury of GI tract. Methods: The Cross-sectional study was conducted on 50 cases admitted in the toxicology ward in Rajiv Gandhi Government General Hospital, madras medical college, Chennai over a period of six months. Patients with history of corrosive ingestion presenting within 24 hours of ingestion subjected to Upper GI endoscopy within 24 hours of admission. Patients presenting after 24 hours, with respiratory distress, suspected perforation either radiologically clinically and normal findings in Upper GI endoscopy were excluded. The patients were serially followed and were subjected for a re-look upper GI endoscopy after 6 weeks and the findings were compared. Results: Corrosive ingestion was more common in the age group 20-30 years and more common in males. Acid ingestion was almost twice as common as alkali ingestion. Suicidal ingestion was the most common circumstance of consumption and associated with higher grade of injury. Patients with ingestion of more than 50 ml had higher grades of injury and also were at higher risk of strictures. The spectrum of injury to the GI tract revealed esophageal injury of grade II b to be the most common finding with the duodenum being spared in majority of the cases. Conclusions: In our study, Patients with ingestion of more than 50ml had higher grades of injury and also were at higher risk of strictures. While the lesser grade injuries (0, I, IIa) were associated with complete recovery with no sequelae, the more severe grades (IIb and IIIa) were associated with higher incidence of strictures especially the circumferential lesions. Oesophageal strictures are commonly associated with suicidal corrosive ingestion. All patients with corrosive ingestion should be subjected to early UGIE and after 6 weeks to identify stricture formation.